RATIONAL POLITICAL BEHAVIOUR ON YOUNG GENERATION VOTER - Abdullah, Mulyana (Universitas Pendidikan Indonesia, 2019)
The advance of political system in Indonesia show that there is the involvement of the political party that is in the interests of each party. It is causing diversity of consideration voters to determine the choice. For Indonesian people today, The rational aspects apparently started to influence the behavior of voters strongly to determine the choice either in general or regional election. The question that arise is hoe the educated young voter, as well as the students of UPI, to choose the leader of government, especially in election? Is the political rationality become the characteristics of their political behaviour? Through the research which is applied the quantitative research approach design and the object be focused in University of Indonesian Education (UPI), revealed that the main aspects which is becomes the consederation of the majority of respondents is vision and mission of political party/candidate. So does with the consideration of the candidate’s experience and performance used as the basis of their decision to vote. Meanwhile, the assessment of political party will be a basis of respondents consideration in determining their choice. It is apparent from their assessment to the political parties that are during compete. So that, it can be conclude that people awareness, especially respondents as the voters show the political attitude critically in examining and assessing vision and mission of politicians. People have participated in politic actively with reviewed the political values of politician’s promises as a form of their rationality of politic.